Pengembangan Mobile Sandbox Berbasis Cyberdeck Untuk Pengujian Keamanan Pada Ponsel Android Menggunakan DNS Proxy dan Port Mirroring - Hariyadi, Dedy; Rosid , Ibnu Abdul; Dewi , Grita Supriyanto (Universitas Muhammadiyah Riau, 2024)
The increase in internet usage in Indonesia has an impact in the form of potential cyber attacks such as malvertising, which is inserting malicious code or malware into advertisements when accessing the internet. In addition to malvertising, other malware activities are also detected in Badan Siber dan Sandi Negara (BSSN) malicious traffic monitoring system. The increase in internet access in Indonesia is also influenced by the growth of smartphone users who are always connected to the internet. The connection of digital devices such as smartphones requires testing of their activities. This study proposes testing the security of internet access on smartphones using the sandbox method. To facilitate testing, a cyberdeck-based mobile sandbox with integrated sensors was developed. The sensors used are malvertising sensors and anomalous traffic. Based on testing of mobile phone activity using the mobile sandbox, smartphones with the vanilla version of the Android operating system have fewer malvertising attacks than those operating systems that have been redeveloped by manufacturers. Although the malvertising attacks are the lowest, they have the potential for anomalous traffic caused by internet access by users or the installation of additional applications.